2022
DOI: 10.21608/jcbr.2022.96763.1233
|View full text |Cite
|
Sign up to set email alerts
|

Ethylenediamine tetra acetic acid (EDTA) enhances the antitumor efficacy of cisplatin against human breast cancer cells in vitro

Abstract: Background: Ethylenediamine tetra acetic acid (EDTA) is used in several biomedical applications. Aim: The aim of this study was to investigate the effect of EDTA treatment on anticancer efficacy of cisplatin (Cis) against human breast cancer (MCF-7) cells in vitro. Materials and Methods: MCF-7 cells were treated either with Cis, EDTA, or their combination for 24h in vitro. The percentages (%) of the inhibitory, and the median inhibitory concentration (IC50) of EDTA were determined by MTT assay. The % of Cis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…In addition, it has been reported that EDTA might prevent iron from forming complex with DOX, which could prevent reactive oxygen species damaging (Duvillard et al, 2004). These results were in line with previous study reported that EDTA could enhance the antitumor efficacy of low dose of Cis in EAC-bearing mice by increasing the percentages of apoptotic tumor cells (El-Naggar et al, 2019;El-Naggar et al, 2022). Furthermore, previous study reported that the treatment with liposomes loaded with EDTA alone did not show any antitumor effects, however, liposomes loaded with EDTA and doxorubicin could significantly reduce drug toxicity without altering the antitumor activity (Song et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, it has been reported that EDTA might prevent iron from forming complex with DOX, which could prevent reactive oxygen species damaging (Duvillard et al, 2004). These results were in line with previous study reported that EDTA could enhance the antitumor efficacy of low dose of Cis in EAC-bearing mice by increasing the percentages of apoptotic tumor cells (El-Naggar et al, 2019;El-Naggar et al, 2022). Furthermore, previous study reported that the treatment with liposomes loaded with EDTA alone did not show any antitumor effects, however, liposomes loaded with EDTA and doxorubicin could significantly reduce drug toxicity without altering the antitumor activity (Song et al, 2014).…”
Section: Discussionsupporting
confidence: 87%